Effect of the temperature in adsorption phenomena of water onto Sub-Bituminous coal (2016)
The presence of water in coal presents a technological challenge for its industrial use in energetic processes. Therefore, this study aims to study the temperature effect on the water adsorption onto coals at 21, 30, 40 and 50°C. A Colombian bituminous coal was used as sample. The coal was characterized by nitrogen adsorption at 77 K (SBET), Scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, elemental analysis (C-H-N elemental). The results showed that the water uptake increased as the vapor pressure increased. The Talu and Meunier model [1] was used to fit the adsorption isotherms, and the mean square root error (MSRE%) was lower than 10%. Additionally, the Gibbs free energy was found to have negative values, which corroborates the spontaneous adsorption process.